2019
DOI: 10.12928/j.reksa.v6i1.1375
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Pengaruh Kinerja Keuangan Dan Corporate Governance Terhadap Kemungkinan Terjadinya Financial Statement Fraud

Abstract: The objective of this research to analyze factors that have impact to financial statement fraud. Independent factors used in this research consists of financial distress, liquidity, leverage, and corporate governance. In other hand, the objective of this research also to analyze the factors that have influence to financial distress. Independent factors used in this research consist of profitability, liquidity, leverage, and corporate governance. Samples is all of manufacturing companies that listed in Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…To show that the local government's financial condition is good, the agent will take any action, including manipulation of the financial statement. The higher the debt to capital asset ratio, the higher of potential for financial statement fraud (Ardhiansyah et al, 2019).…”
Section: The Influence Of the Debt To Capital Asset Ratio On Financia...mentioning
confidence: 99%
“…To show that the local government's financial condition is good, the agent will take any action, including manipulation of the financial statement. The higher the debt to capital asset ratio, the higher of potential for financial statement fraud (Ardhiansyah et al, 2019).…”
Section: The Influence Of the Debt To Capital Asset Ratio On Financia...mentioning
confidence: 99%
“…Williams & Adeyanju, (2021) Kinerja keuangan mempengaruhi fraud dengan melihat nilai profitabilitas yang mendorong para pelaku untuk melakukan fraud. Oleh karena itu, tingkat hutang meningkatkan tekanan pada manajemen untuk melakukan fraud (Ardhiansyah et al, 2019). Sesuai dengan teori agensi dimana pemegang saham tidak tahu lebih banyak tentang perusahaan daripada pengelola.…”
Section: Kinerja Keuangan Terhadap Fraudunclassified
“…The research results showed that changes in financial objectives and the financial stability of the auditor had a significant positive impact on financial statement fraud. Ardhiansyah et al (2019) conducted a study on all manufacturing companies listed on the Indonesia Stock Exchange (BEI) and discovered that financial distress, liquidity, leverage, and corporate governance have a significant impact on financial statement fraud. Li (2020) utilized a Back-Propagation Neural Network (BPNN) to develop a financial identification model for detecting instances of financial fraud in publicly traded companies.…”
Section: Introductionmentioning
confidence: 99%